2021
DOI: 10.4085/1062-6050-0330.21
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Navigation of Black and White Adolescents After Sport-Related Concussion: A Path Toward Health Equity

Abstract: Context: Care-seeking behaviors for sport-related concussion (SRC) are not consistent across demographic subgroups. These differences may not only stem from health inequities but can further perpetuate disparities in care for SRCs. Objective: To determine whether racial differences exist in the care pathway from injury to SRC clinic within adolescent athletes. Design: Retrospective cohort Setting: Regional SRC center Participants: Of 582 total athlete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Our study provides broader data assessing adherence among pediatric patients presenting to their PC provider for any injury mechanism and identifying sociodemographic and socioeconomic differences in completion of care. A study by Wallace et al39 assessed patterns of healthcare navigation among Black and White adolescents following a sports-related concussion. Contrary to our study, they found few differences between Black and White athletes in initial contact and presentation to healthcare, referral patterns, and follow-up rates within a concussion clinic, despite fewer Black athletes having private insurance than White athletes 39.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study provides broader data assessing adherence among pediatric patients presenting to their PC provider for any injury mechanism and identifying sociodemographic and socioeconomic differences in completion of care. A study by Wallace et al39 assessed patterns of healthcare navigation among Black and White adolescents following a sports-related concussion. Contrary to our study, they found few differences between Black and White athletes in initial contact and presentation to healthcare, referral patterns, and follow-up rates within a concussion clinic, despite fewer Black athletes having private insurance than White athletes 39.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Wallace et al39 assessed patterns of healthcare navigation among Black and White adolescents following a sports-related concussion. Contrary to our study, they found few differences between Black and White athletes in initial contact and presentation to healthcare, referral patterns, and follow-up rates within a concussion clinic, despite fewer Black athletes having private insurance than White athletes 39. Wallace et al39 suggest one potential reason for this outcome could be that participating in school sports may facilitate better access to healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…Emergency department utilization in youth and adolescents is multi‐factorial and often include access to physician care, insurance status, transportation difficulties, and cultural and language barriers 35 . Other potential influences include injury reporting, 36 athlete and caregiver literacy, 37,38 and health care navigation 39 . These dynamics seem to increase the emergency department use for both initial and follow up care and often create a delay in receiving care 35 .…”
Section: Discussionmentioning
confidence: 99%
“… 35 Other potential influences include injury reporting, 36 athlete and caregiver literacy, 37 , 38 and health care navigation. 39 These dynamics seem to increase the emergency department use for both initial and follow up care and often create a delay in receiving care. 35 Using emergency care services for an initial diagnosis has the potential to delay access to a provider who can offer specialty treatment for the athlete's condition and may influence the timeline for recovery from injury.…”
Section: Discussionmentioning
confidence: 99%
“…Median household incomes follow a similar trend, with the highest median incomes reported by Asian households, followed by White and Black (11). Beyond educational attainment and financial security, race and SES often carry unique perspectives and life experiences, including racial discrimination, marginalization, and microaggressions, which may influence SRC knowledge (13), reporting (13), access to healthcare (14), and injury outcomes (15). Indeed, contemporary literature appraising the relationship between race and SRC recovery has resulted in heterogeneous findings across the intersections of age, sex, and sport contact level(s) (15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%